Pengaruh Citra Merek dan Promosi Terhadap Loyalitas Pelanggan dan Keputusan Pembelian sebagai Variabel Mediasi PT. Matahari Departemen Store - Dicky Wahyu Prasetyo; Wahyu Murti (Jurnal Manajemen FE-UB, 2021)
AbstractThe data used in this study are primary data which collected from respondents' answersbased on the questionnaire given, namely as many as 100 people. The data processing methoduses the path analysis method (Path Analysis) with the help of SPSS version 21.0. Statistical testusing the individual parameter significance test (t test) and the significance test simultaneous(Test F).The results showed that simultaneously the brand image variable, promotion and customersatisfaction have a significant effect on loyalty customer. Partially shows that analysis 1: brandimage variable significant effect on customer loyalty, while analysis 2: promotion variables havea significant effect on customer loyalty and on analysis 3: the purchase decision variable has asignificant effect on performance customer loyalty.Keywords: Brand image, Promotion, Purchase Decision, Loyalty